Anti-N-Methyl-D-Aspartate Receptor Encephalitis: A Review and Neuropsychological Case Study. Issue 1 (2nd January 2016) - Loughan, Ashlee R.; Allen, Aislyn; Perna, Robert; Malkin, Mark G.
Abstract : Objective : Anti- N -Methyl-d -Aspartate Receptor (NMDAR) Encephalitis is an autoimmune-mediated encephalitis, which may be associated with a tumor, which occurs when antibodies bind central NMDA receptors. Although typically diagnosed in women, approximately 20% of cases have been males. Due to the challenges with identification, imaging, and diverse symptom presentation, this syndrome is often misdiagnosed. Accurate diagnosis may provide an opportunity for introduction of disease-modifying therapies, which may alter disease trajectory. Moreover, neuropsychology has yet to fully clarify the pattern of impairments expected with this disorder. Methods : This manuscript reviews a single case study of a 42-year-old male diagnosed with NMDAR encephalitis. Neuropsychological evaluation was completed subsequent to diagnosis, treatment, and rehabilitation. Ongoing patient complaints, approximately six months post diagnosis, included reduced sustained attention, poor word retrieval, and daily forgetfulness. Adaptive skills were improved following rehabilitation. Results : Direct testing revealed mildly impaired sustained attention, processing speed, oral word fluency, and executive functioning. All other cognitive domains were within estimated premorbid range, low average to average. Conclusions : Neuropsychological deficits were consistent with mild frontal brain dysfunction and continued recovery. This case illustrates the need for medical and psychological practitioners to understand NMDAR encephalitis, its symptom presentation, and related neuropsychological impact; particularly with the potential for misdiagnosis.